WHAT DO THE HIGHLY-RATED AND ACCREDITED LIS PROGRAMMES INFORM US ABOUT EDUCATION IN DIGITAL LIBRARIES? - A., Abrizah; A., Noorhidawati,; M. R., Hilmi; D., Azeana (Malaysian Journal of Library and Information Science, 2009)
This paper examines the course offerings in digital library (DL) education, guided by the following specific research question: â€œWhat do the Library and Information Science (LIS)-accredited programmes inform us about education in digital libraries?â€ The paper provides an analysis of DL education which is included in the curriculum of 13 accredited and highly-rated library schools. Findings indicate that a significant DL content is present in the curriculum; and the inclusion is categorised into (a) an independent or full digital library course, (b) an integrated digital library course with other LIS topics, and (c) courses with close relation to DL processes. The title â€œDigital Libraries" appears to be the most popular title in the USA LIS schools sampled, and range from theory and practice, to project-based courses. The four UK LIS schools sampled do not have an explicit focus on DL topics. The curriculum areas for DL education suggested by Spinks and Cool (1999) are taken into account in analysing the content of the DL courses offered by the library schools. The paper also provides insights into the current state of DL education in Malaysia, and reports the findings of a small-scale survey, which has informed the LIS programme on how the DL course should be conducted. Findings from this paper may assist DL educators to develop DL modules and courses, standing on a solid foundation as well as following a standard curriculum design model of analysis, design/development, and evaluation practised by the renowned LIS schools worldwide.